2012
DOI: 10.1021/es3015138
|View full text |Cite
|
Sign up to set email alerts
|

Oil Weathering after the Deepwater Horizon Disaster Led to the Formation of Oxygenated Residues

Abstract: Following the Deepwater Horizon disaster, the effect of weathering on surface slicks, oil-soaked sands, and oil-covered rocks and boulders was studied for 18 months. With time, oxygen content increased in the hydrocarbon residues. Furthermore, a weathering-dependent increase of an operationally defined oxygenated fraction relative to the saturated and aromatic fractions was observed. This oxygenated fraction made up >50% of the mass of weathered samples, had an average carbon oxidation state of −1.0, and an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
371
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 296 publications
(402 citation statements)
references
References 48 publications
28
371
0
3
Order By: Relevance
“…15,18,20,21 Aeppli and colleagues noted the apparent recalcitrance of sand patties and characterized their chemical composition. 20 They reported that >50% of the mass of the material in these structures is not hydrocarbon at all, but oxygenated hydrocarbon-derived chemical features produced through a combination of weathering processes. We questioned the environmental fate and impact of these residual oil structures, and considering their deposition in the beach swash zone, explored the susceptibility of sand patties to the most likely forms of advanced decomposition -photoxidation and biodegradation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15,18,20,21 Aeppli and colleagues noted the apparent recalcitrance of sand patties and characterized their chemical composition. 20 They reported that >50% of the mass of the material in these structures is not hydrocarbon at all, but oxygenated hydrocarbon-derived chemical features produced through a combination of weathering processes. We questioned the environmental fate and impact of these residual oil structures, and considering their deposition in the beach swash zone, explored the susceptibility of sand patties to the most likely forms of advanced decomposition -photoxidation and biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, the transformation of the crude Macondo 252 oil resulted in the formation of a group of partially oxidized organic compounds collectively termed 'oxyhydrocarbons.' 20 The formation of the oxyhydrocarbons was coincident with a decrease in the fraction of n-alkanes and aromatic compounds in the residue. These oxyhydrocarbons are most obviously found in sand patties that wash up in the swash zone of northern GoM beaches due to prevailing winds and currents.…”
Section: Chapter 1 Introductionmentioning
confidence: 95%
See 3 more Smart Citations